PERENCANAAN STRATEJIKPENDIDIKAN UNTUK MENINGKATKAN KETERAMPILAN HIDUP SISWA BERKEBUTUHAN KHUSUS TIPE B DI SLB NEGERI PURWAKARTA - virgo, Agus; Handayani, sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the implementation of strategic educational planning in improving life skills for students with hearing impairments (Type B) at SLB Negeri Purwakarta. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that the school has formulated its strategic planning based on the POAC (Planning, Organizing, Actuating, Controlling) management model. The school identifies students' needs and develops life skills programs including self-care, cooking, and handicrafts, supported by visual and experiential learning methods. Although implementation and informal evaluations have shown positive impact on students’ independence and confidence, the documentation and formal assessment systems require further development. This strategic planning model has the potential to be a reference for inclusive schools in developing adaptive, functional, and sustainable life skills education for students with special needs. Keywords: Strategic Planning, Life Skills Education, Special Needs Students, POAC, Inclusive Education